8 marzo 2023 Casa abierta Marketing video 3 - Aviles Quijano, Jaime Eduardo (2023)
MARCH 8, 2023 OPEN HOUSE MARKETING VIDEO 3 BY THE STUDENTS OF THE FACULTY OF ADMINISTRATIVE SCIENCES OF THE STATE UNIVERSITY OF BOLÍVAR